Effectiveness of Psychological Counseling on Anxiety Levels among Post-Abortion Mothers in Primary Health Facilities - Rhina Chairani Lubis; Susanti Susanti (Yayasan Media Utama Sains, 2025)
Objectives: This study aims to analyze the effectiveness of psychological counseling in reducing anxiety levels among post-abortion mothers in primary healthcare facilities in the Batam Kota District. Methods: This study used a quantitative pre-experimental design with a one-group pretest-posttest approach. A total of 30 post-abortion mothers were selected using purposive sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale (HARS) before and after the intervention. The psychological counseling intervention was conducted through structured sessions focusing on emotional support, problem exploration, and coping strategies. Data were analyzed using a paired sample t-test after normality testing with the Shapiro–Wilk test. Results: The results showed a significant decrease in anxiety levels after psychological counseling. The mean anxiety score decreased from 25.47 (SD = 4.12) before the intervention to 17.63 (SD = 3.58) after the intervention. The distribution of anxiety levels also improved, with the majority of respondents shifting from moderate (50%) and severe (36.7%) anxiety categories to mild anxiety (53.3%) after counseling. Statistical analysis revealed a significant difference between pretest and posttest scores (p = 0.000), indicating the effectiveness of the intervention. Conclusions: Psychological counseling is effective in reducing anxiety levels among post-abortion mothers. Therefore, integrating counseling services into post-abortion care in primary healthcare settings is recommended to improve women's psychological well-being.